COMPARATIVE STUDY OF IMAGES IN THE EPICS "YAKKA AHMAD AND ERNAZARKHAN" - Tulaganova Nilufar (Galaxy International Interdisciplinary Research Journal, 2021)
The images of the epics "Yakka Ahmad and Ernazarkhan," which are essential in Uzbek folklore,are compared in this article. Master’s students, independent researchers, and doctorate students should read this article.